Classroom Ice Breaking: An Analysis of the Impact of Ice Breaking on the Social Studies Learning Process at SMPN 1 Sutera - Mariska, Maisya; Harisnawati, Harisnawati (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This research was motivated by low student enthusiasm and concentration in Social Studies (IPS) learning at SMP Negeri 1 Sutera, Pesisir Selatan Regency. This condition is evident in the high number of students exhibiting symptoms of boredom, such as wandering in and out of class, feeling sleepy, and being inactive during the learning process. This study aims to analyze the impact of implementing icebreakers on the Social Studies learning process, specifically in improving attention, concentration, and creating a pleasant learning atmosphere in grade VIII.6. This research used a qualitative approach with a field study method. Data were collected through observation, in-depth interviews, and documentation studies with 11 informants consisting of curriculum representatives, Social Studies teachers, Civics teachers, and students in grades VIII.6 and VIII.5. Data analysis used the Miles and Huberman interactive model, which includes data reduction, data presentation, and conclusion drawing. The results showed that the implementation of icebreakers had a positive impact on the Social Studies learning process. Students became more focused, active, and enthusiastic in participating in the learning process. The classroom atmosphere became more dynamic and enjoyable, thereby reducing boredom and increasing interaction between teachers and students. Thus, ice breaking has proven to be effective as a strategy to create interactive and meaningful learning.